MATLAB Answers

Writing a loop instead of sum

2 views (last 30 days)
Fred
Fred on 3 Oct 2012
Hello,
n=40; b=1; m=6; s=0.15
for k=1:(n-(2*b)-m+1)
c=L(k+1:k+m-1);
if sum(abs(c-L(k)))<=2*s %How can I use a loop instead of this sum
lam_d=(1/m)*sum(L(k:k+m-1));
break
end
end
I have problem with line starting with sum, can anybody tell me how can I use a loop instead of sum?
Thank you

  0 Comments

Sign in to comment.

Accepted Answer

Image Analyst
Image Analyst on 4 Oct 2012
In general, to sum up a value in a loop
theSum = 0;
for k = 1 : whatever
theSum = theSum + theVectorValues(k);
end
I don't know why you can't just use sum(), but just adapt this into your code. Be careful not to call your sum "sum" or you'll blow away the built-in sum() function.

  1 Comment

Fred
Fred on 4 Oct 2012
Thank you, I realized that I had used sum in other lines as a parameter so it was the making problem :)

Sign in to comment.

More Answers (0)

Sign in to answer this question.

Products


Translated by